A critical analysis of the role of aid agencies in the Kenyan land policy process (1999-2012) - Mrewa, Bernard (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
Land is central to development policies globally, including with reference to Africa, but the land reform strategies and modalities often pursued by international development agencies are controversial in terms of their potential and actual impact on questions of land rights, possession and access as well as poverty reduction and economic development. In the current era of global neoliberal restructuring, as indeed in the past, international aid agencies (or donors) have identified the formation and reform of national land policies in Africa and elsewhere as crucial in terms of facilitating systematic and successful land reform measures. A practical example of this is the case of Kenya. In this context, this thesis seeks to critically analyse the role of development (or aid) agencies in the land policy-making process in Kenya from 1999 to 2012. In this regard, the thesis does not focus on the product of the policy process (i.e. the land policy) let alone the implementation or impact of the policy. Rather, it treats the policy process itself as worthy of investigation and analysis, and thus delves into the policy processes leading to the product (the Kenyan land policy). The involvement of aid agencies in land policy in Kenya is part of a broader pattern of development cooperation with the Kenyan state over an extended period of time. Despite this long-term integration of Kenya in the international development system and the direct and pronounced involvement of global donors in the land policy-making process in Kenya, land policy outcomes in Kenya cannot be reduced simply to the influence and power of these donors. While the thesis analyses in detail the various forms of donor input into the land policy process, it also highlights that other (Kenyan-based) actors were centrally involved in the land policy formation process in the country, including state bureaucrats and national politicians but also a diverse range of interests embedded in civil society. Development agency involvement in the land policy process can be only understood in relation to these other actors. In Kenya, donors in fact interacted with these other actors in complex and fluctuating ways as they sought to maximise their influence in the national land policy process, and the thesis examines these dynamic and sometimes turbulent social and political interactions. These interactions were further complicated in Kenya because of the highly-ethnicised character of national politics and the fact that the constitution-review process was taking place at the same time as the land policy process. Together, this meant that the land policy process at nation-state level in Kenya became both a focus and site of struggle between state and non-state actors (including donors).
Keywords: Uncatalogued